2014
DOI: 10.1155/2014/943538
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Deposition of Te and Se on Flat TiO2for Solar Cell Application

Abstract: Te and Se layers were deposited on〈glass/FTO/flat-TiO2〉by electrochemical deposition. The Te-Se-stacked layer was annealed at 200°C, and then, the migration of Te into the Se layer by annealing was confirmed using auger electron spectroscopy (AES), which was performed by Te doping on the Se layer. Au back contact was coated by vacuum deposition on the Te-doped Se layer, resulting in superstrate-structured solar cells of〈glass/FTO/flat-TiO2/Se-doped Te/Au〉with a 0.50 V open-circuit voltage, 6.4 mA/cm2photocurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…19 Ito et al recently prepared an extremely thin Se absorber layer on mesoporous TiO 2 (mp-TiO 2 ) and successfully constructed one solar cell with ITO/compact-TiO 2 /mp-TiO 2 /Se/Au, which achieved over 3% PCE without any expensive organic parts. 20,21 However, to date, utilization of Se as a photoabsorber in HSCs has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…19 Ito et al recently prepared an extremely thin Se absorber layer on mesoporous TiO 2 (mp-TiO 2 ) and successfully constructed one solar cell with ITO/compact-TiO 2 /mp-TiO 2 /Se/Au, which achieved over 3% PCE without any expensive organic parts. 20,21 However, to date, utilization of Se as a photoabsorber in HSCs has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, selenium is also a key element for current high-performance chalcogenide-based solar cells, for example CuInSe 2 and Cu 2 ZnSnSe 4 . However, it is relatively difficult to precisely control the composition of ternary or quaternary systems compared to a single element; therefore, it is attractive to further investigate the potential of elemental selenium. It is well-known that selenium is a p-type semiconductor, and studies have shown that selenium has bipolar transport properties and can work as a great transporter as well as light absorber. , In addition, inorganic c-Se has better stability than most solution processable photovoltaic materials including organic solar cells (OPV) and organic–inorganic hybrid perovskite solar cells. According to the Shockley–Queisser limit, the maximum theoretical efficiency of selenium solar cells is estimated to be about 20% under AM 1 …”
mentioning
confidence: 99%
“…It is well-known that selenium is a p-type semiconductor, and studies have shown that selenium has bipolar transport properties and can work as a great transporter as well as light absorber. 6,7 In addition, inorganic c-Se has better stability than most solution processable photovoltaic materials including organic solar cells (OPV) and organic−inorganic hybrid perovskite solar cells. 8−14 According to the Shockley−Queisser limit, the maximum theoretical efficiency of selenium solar cells is estimated to be about 20% under AM 1.…”
mentioning
confidence: 99%
“…Some of these drawbacks include (i) the low solubility of the functional electrolytes (compounds containing silicon, tellurium, selenium) in water/organic electrolytes (ii) non-adherence of the films/coatings on the substrate materials (iii) solubility of the electrodeposited material/coating in the electrolyte and (iv) formation of relatively thin deposits/coatings. For example, tellurium coatings prepared from aqueous solutions including ionic liquids, were reported to be of inferior quality [11][12][13]. These coatings, when prepared from a ternary chloride melt (AlCl 3 -NaCl-KCl, using TeCl 4 as the functional electrolyte), have also been observed to suffer from similar inadequacies.…”
Section: Introductionmentioning
confidence: 99%